Islamic Education Based on Agroforestry in MTs Pakis Gununglurah Cilongok Banyumas - Sumiarti Sumiarti (Ijtimā`iyya: Journal of Muslim Society Research, 2017)
The paper aims to describe the implementation of Islamic education in Madrasah Tsawaniyah (MTs PAKIS) located on the edge of the forest of Mount Slamet village of Gunung Lurah Cilongok Banyumas Subdistrict. MTs PAKIS is a private MTs established by volunteers who care about the high number of primary and secondary drop outs of children from the edge of the forest. Poverty, low awareness of education, limited access to transportation and infrastructure make it possible for rural residents not to receive inherited educational services from generation to generation. MTs PAKIS is expected to be one of the alternatives to provide Islamic education-based secondary education services that can make school-aged children and forest-edge communities better educated and improve their quality of life. In order for the education process is not uprooted from the roots of the community, MTs PAKIS held gricultural-based learning process and forestry or agrofrestry.